2016
DOI: 10.3847/1538-4357/833/2/207
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Filamentary Structures Around the Virgo Cluster Revisited

Abstract: We revisit the filamentary structures of galaxies around the Virgo cluster, exploiting a larger dataset based on the HyperLeda database than previous studies. In particular, this includes a large number of low-luminosity galaxies, resulting in better sampled individual structures. We confirm seven known structures in the distance range 4 h −1 Mpc < SGY < 16 h −1 Mpc, now identified as filaments, where SGY is the axis of the supergalactic coordinate system roughly along the line of sight. The Hubble diagram of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 41 publications
2
66
0
1
Order By: Relevance
“…Zhang et al 2015) and M87 deviating from the mean of the velocity distribution of galaxies, Binggeli et al (1987) concluded that even the Virgo cluster core is a dynamically young structure. Moreover, using the large number of low-mass galaxies has led to confirming several previously known structures around Virgo (Tully 1982) as filaments that likely feed the cluster with newly infalling galaxies (Kim et al 2016), similar to the findings of Adami et al (2009) for the Coma cluster.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Zhang et al 2015) and M87 deviating from the mean of the velocity distribution of galaxies, Binggeli et al (1987) concluded that even the Virgo cluster core is a dynamically young structure. Moreover, using the large number of low-mass galaxies has led to confirming several previously known structures around Virgo (Tully 1982) as filaments that likely feed the cluster with newly infalling galaxies (Kim et al 2016), similar to the findings of Adami et al (2009) for the Coma cluster.…”
supporting
confidence: 73%
“…Galaxies that are likely members of the so-called M and W clouds, located at a distance of 32 Mpc (Gavazzi et al 1999) in the western part of Virgo, are excluded from our working sample. This is also justified because the W-M-Sheet that encompasses those clouds is unlikely to be dynamically connected to Virgo (Kim et al 2016). Following Gavazzi et al (1999), our exclusion criterion is that a galaxy lies in the projected region of one of the clouds and has a velocity v LG relative to the Local Group larger than 1900 km s −1 (with v LG = v heliocen.…”
Section: Observational Datamentioning
confidence: 99%
“…Studies at high redshift (Fadda et al 2008;Geach et al 2011;Coppin et al 2012;Darvish et al 2014) as well as z ∼ 0 (e.g. Porter et al 2008;Mahajan, Haines, & Raychaudhury 2010;Haines et al 2011;Alpaslan et al 2016;Kim et al 2016;Kleiner et al 2017;Kuutma, Tamm, & Tempel 2017;Kraljic et al 2018) have now shown that the intermediate density environment prevalent in filaments not just bridge the gap between the dense interior of clusters and 'voids' devoid of galaxies, but play a rather important role in modulating galaxy observables. Owing to the highly coherent flow of galaxies along the filaments (González & Padilla 2009), they have not just been observed at all wavelengths ⋆ E-mail: smritimahajan@iisermohali.ac.in from ultraviolet (UV) (Gallazzi et al 2009;Geach et al 2011;Coppin et al 2012) to infrared (Fadda et al 2008;Haines, Gargiulo, & Merluzzi 2008) by direct methods such as quantifying the distribution of galaxies, thermal Sunyaev-Ze'ldovich (tSZ) effect (Bonjean et al 2018) and weak gravitational lensing (Dietrich et al 2012;Jauzac et al 2012), but also indirectly using a bent double lobe radio source (Edwards, Fadda, & Frayer 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…See also the discussion by Kim et al (2016). For the moment, we draw attention to the concentration of galaxies to the left of the Virgo Cluster, a structure de Vaucouleurs (1961) has called the Virgo Southern Extension.…”
Section: The Virgo Associationmentioning
confidence: 99%